Modifying the conceptual model of site selection in the organisation of association conferences. Issue 5 (19th October 2020) - Nolan, Emma
Abstract: International association conferencing is the largest and most profitable segment of the events industry. Competition to host these events is fierce and many destination management organizations (DMOs) offer a range of incentives to attract professional meeting planners to their destination. Many second-tier destinations have invested in their facilities and incentives in order to compete with more traditional conference cities. However, to date there has been a limited exploration of the process of destination or site selection. Prior research has generated conceptual models of site selection, which, though insightful, do not adequately reflect the role of DMOs in the process. A critical evaluation of these models and the supporting literature on site selection has provided the basis for a qualitative inquiry which has involved twenty-five elite professionals (meeting planners and DMO staff). The results from the interviews has led to the creation of an amended conceptual model of site selection which incorporates Weber's (2001 . Meeting planners' use and evaluation of convention and visitor bureaus. Tourism Management, 22(6), 599–606) list of DMO services and draws particular attention to the role of subvention in site selection.